2007
DOI: 10.1111/j.1750-3841.2007.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Size of Cellulose Granules on Dough Rheology, Microscopy, and Breadmaking Properties

Abstract: Breadmaking was performed with cellulose-blended wheat flour. Cellulose granules (7 types) of various sizes (diameter) were prepared by kneading. With increase of the blend percent of the cellulose samples from 10% to 20%, breadmaking properties such as bread height and specific volume (SV) gradually decreased in every sample; however, the decreasing levels of the properties in 7 types of various sizes varied. The decrease of bread height and SV was associated with the size of the cellulose granule. It was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 9 publications
4
26
0
2
Order By: Relevance
“…They applied a mixiograph test of cellulose granuleblended wheat flour dough to elucidate the effect on breadmaking properties of larger cellulose granules. 3) Cellulose granules with a diameter above 154 mm blended with wheat flour resulted in almost the same profile for the mixogram as that of wheat flour; i.e., the profile had a short mixing requirement and showed a viscous gluten matrix, 3) these being necessary for good breadmaking properties. However, cellulose granules with a diameter below 81 mm blended with wheat flour produced a different curve showing non-continuous and non-viscous dough due to breakdown of the gluten protein, as confirmed by microscopy of the cellulose granule/wheat flour dough stained with protein dye (coomassie brilliant blue).…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…They applied a mixiograph test of cellulose granuleblended wheat flour dough to elucidate the effect on breadmaking properties of larger cellulose granules. 3) Cellulose granules with a diameter above 154 mm blended with wheat flour resulted in almost the same profile for the mixogram as that of wheat flour; i.e., the profile had a short mixing requirement and showed a viscous gluten matrix, 3) these being necessary for good breadmaking properties. However, cellulose granules with a diameter below 81 mm blended with wheat flour produced a different curve showing non-continuous and non-viscous dough due to breakdown of the gluten protein, as confirmed by microscopy of the cellulose granule/wheat flour dough stained with protein dye (coomassie brilliant blue).…”
mentioning
confidence: 97%
“…Seguchi et al 3) have reported that the reason why bread baked with smaller uncharred cellulose granules (6-154 mm) and wheat flour gave inferior bread-making properties to those baked with larger uncharred cellulose granules (154-650 mm) and wheat flour was that the smaller uncharred cellulose granules interfered with the formation of a gluten matrix which was apparent from a mixograph test and microscopic observation; they also observed from a fermograph test that the amount of gas released from uncharred cellulose granules contained in the bread dough increased with decreasing size of the uncharred cellulose granules below 154 mm. The mixograph test and microscopic abservation in this experiment were performed with charred cellulose granules of 6 or 650 mm and wheat flour and the same results were obtained (data are not shown here).…”
Section: Effect Of Charred Cellulose Granules On the Breadmaking Propmentioning
confidence: 99%
See 3 more Smart Citations